TEACHER’S FEEDBACK IN TEACHING SPEAKING - Aini, Luluk Rahmatia Trisna; Rochmahwati, Pryla (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
This research deals with teacher’s feedback in teaching speaking at the seventh grade of SMPN 4 Ponorogo. This research was conducted for several purposes. They are: 1) to know the implementation of teacher’s feedback in teaching speaking at the seventh grade of SMPN 4 Ponorogo, 2) to know students’ response to the teacher’s feedback in teaching speaking at the seventh grade of SMPN 4 Ponorogo. The researcher applied qualitative research approach and the case study was the research design. In this research, the researcher analyzed the data by Mattew B Miles and Michael Hubberman’s; data reduction, data display, and conclusion and verifications data.  It is a methodological on data analysis which involved an interview, an observation, and a documentation. Then both English teacher and the students especially 7G and 7H classes of SMPN 4 Ponorogo were the source and the object of this study. The findings of this study clarified that: (1) the English teacher implemented this feedback by giving tasks and inviting performance. Starting by the teacher chose the task and read the task to give the example of how to pronounce the words. Then the students should immitate it and improve their speaking of what they have took from the text in front of the class. While enjoying the students’ performance, the teacher took the scores and gave the feedback. It concluded on oral and written feedback. Something difference on this point than other points of feedback, the teacher applied on excellent point which is same as 10 scores in 1 point. Focusing on lower students to motivate their English skills and upgrading the students (the middle and the upper one) were the teacher’s goal in this strategy implementation. (2) the students’ response was very positive. It is shown when the researcher looked at the students were very active during doing the assignments. Through this feedback, the students can get several points in learning English such as feeling motivated and appreciated, getting an active assessment, and getting additional scores to upgrade their low scores. In the end, the researcher concluded that the teacher’s feedback applied positively in increasing students’ speaking ability.